Introduction to Hospital Infection Control and Hand Hygiene - R. Harsvardhan; Tulika Gupta (Emerging Trends in Disease and Health Research Vol. 9, 2022)
Hospital infection control program with stable structure should be present in all institutions that provide health care in order to create a managed environment. Infection control is the discipline which is concerned with preventing health care associated infection; it is a vital; though often non-supported and not recognized as a part of the organization of the healthcare. Health care associated infections are drawing increasing attention from patients, insurers, governments and regulatory bodies. This is not only because of the magnitude of the problem in terms of the associated morbidity, mortality and cost of treatment, but also due to the growing recognition that most of these are preventable. Hospital Infection control is very essential for the safety and wellbeing of patients, hospital staffs and visitors of the hospital. Hospital administrators should strive to create an organizational atmosphere in which adherence to recommended Hospital infection control practices is considered an integral part of providing high-quality care. For such an approach to be successful, hospitals must provide visible support and sufficient resources in the form of continuous education and training programs.